2008
DOI: 10.1167/iovs.07-0451
|View full text |Cite
|
Sign up to set email alerts
|

Induction by Latanoprost of Collagen Gel Contraction Mediated by Human Tenon Fibroblasts: Role of Intracellular Signaling Molecules

Abstract: Latanoprost induced collagen gel contraction mediated by HTFs. This action of latanoprost appeared to depend on the formation of stress fibers and the activation of MAPKs, FAK, Rho-associated kinase, phospholipase C, and MLC kinase in HTFs. Latanoprost may therefore influence subconjunctival wound healing by affecting the contractility of Tenon fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 45 publications
2
34
0
Order By: Relevance
“…It has been reported that MAPK inhibitors (JNK, ERK, or p38 inhibitors) inhibit gel contraction mediated by fibroblasts [29,30,31]. In the current study, we investigated the role of MAPKs in regulating endothelial cell-mediated collagen gel contraction in response to TNF-α stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that MAPK inhibitors (JNK, ERK, or p38 inhibitors) inhibit gel contraction mediated by fibroblasts [29,30,31]. In the current study, we investigated the role of MAPKs in regulating endothelial cell-mediated collagen gel contraction in response to TNF-α stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, these results are in accordance with a previous report on HTF cells showing that latanoprost-induced HTF CPCG contraction was dependent on p38 activation but also seemed mediated by ERK and c-Jun Nterminal kinase signaling. 53 In another study, p38 inhibition blocked TGF-b-mediated HTF CPCG contraction and myofibroblast transition while ERK signaling inhibition, by U0126, induced a spontaneous contraction of HTF CPCG. 52 Hence, we extended these observations made on HTF to TM cells and showed that latanoprost induced the generation of contractile forces in TM cells, a characteristic of myofibroblast phenotype, through ROCK and p38 activation.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies using CPCG as a force-sensing device showed that latanoprost induced contraction of human Tenon fibroblasts (HTF) from the conjunctiva and correlated with the formation of actin stress fibers, consistent with our observations. 53 In contrast, endothelin-dependent short-time contraction of bovine TM strips has been reported to be inhibited by FP receptor agonists, suggesting that the FP receptor activation could potentially lead to opposite effects at shorter time points. 54 Finally, EP2 receptor activation decreased CPCG contraction by dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 98%
“…The cells from each patient were cultured separately in MEM supplemented with 10% FBS, and they were used for the present study after 3 to 7 passages. 10 Assay of IL-6, IL-8, and MCP-1 Release Assays were performed as described previously. 12 HTFs were cultured in 24-well plates until they achieved confluence, after which the culture medium was replaced with serum-free MEM for 1 day.…”
Section: Isolation and Culture Of Htfsmentioning
confidence: 99%
“…7 Various studies have investigated the effects of antiglaucoma drugs on Tenon's capsule fibroblasts, [8][9][10] which contribute to the inflammatory response in the conjunctiva and to wound healing after glaucoma filtration surgery. We previously showed that latanoprost induced collagen gel contraction mediated by Tenon's capsule fibroblasts 10 or corneal fibroblasts.…”
mentioning
confidence: 99%